Neo-Gothic Architectural Style at Hati Kudus Yesus Church in Malang City - Manalu, Citra; Ema Yunita Titisari (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2025)
Hati Kudus Yesus or Kayutangan Church is a colonial building in Kayutangan historical tourism area of ??Malang City which is the only building for worship with a distinctive architectural style, namely Neo-Gothic. This study aim to reveal the significance and application of Neo-Gothic architectural style in the church. In addition, this study also reveals the meaning contained in Neo-Gothic architectural elements which have never been discussed in depth by previous studies. Literature review was conducted to formulate characteristics of each Neo-Gothic unit observation, sign’s classification based on objects, and the meaning of Neo-Gothic as church architecture. Field data were obtained through triangulation process, namely observation, interviews, and documentation. Results show that Kayutangan Church has a significant Neo-Gothic architectural identity because it meets 69% of all characteristics standards that focus more on visual and symbolic applications than structural and spatial applications. Religious symbolism is the most dominant meaning in the church’s architectural elements and is most visible in elements with symbolic sign types. Analysis through three stages produce formulation of appropriate preservation actions for Neo-Gothic architectural elements that include aspects that can be changed and cannot be changed as well as the extent to which preservation efforts can be carried out. Keywords: Kayutangan church, Neo-Gothic, meaning, sign